Kajian Sosial Ekonomi Sengketa Lingkungan Berbasis Ekosistem - Widya Andharie Rahasthera (ECOTAS, 2021)
The decline in environmental quality is often related to public complaints about the impact of the decline in quality. The impact of environmental degradation that causes an influence on the socio-economic life of the community often causes conflict. This article aims to explain the concept of an ecosystem approach as part of a more comprehensive and holistic analysis of environmental conflicts. Analysis and mapping of stakeholders in the ecosystem approach is an important part of mapping conflict in the socio-economic aspects to get a complete picture so that it can help efforts to resolve the conflicts by taking into account the local context.